Affordability of fruits and vegetables in Ethiopia - Hirvonen, Kalle; Wolle, Abdulazize; Minten, Bart (International Food Policy Research Institute, 2018)
As in many other low-income countries, fruit and vegetable (FV) consumption is very low in Ethiopia. Consequently, micronutrient deficiencies, such as for Vitamin A, are widespread, and more than half of young Ethiopian children suffer from anemia. Efforts to increase FV consumption in Ethiopia have focused on improving consumer knowledge of the health benefits of FV and other nutritious foods. While these interventions have been successful in improving knowledge and ultimately improving dietary diversity, diets remain extremely monotonous across the country. Recent international research in this area suggest that high relative prices of FVs could be another important constraint. To shed more light on this issue, we assess the affordability of FVs in Ethiopia. Using expenditure and price data collected by the Central Statistical Agency of Ethiopia, we find that the average Ethiopian household would have to spend 11 percent of their income to meet the international recommendation of two servings of fruits and three servings of vegetables per person per day. This share is more than 2.5 times higher for households in the poorest quintile, indicating that meeting these guidelines is currently out of reach for the poorest households in Ethiopia. More investments and research attention to the production of fruits and vegetables is urgently needed to improve supplies and, hence, their affordability.